2001
DOI: 10.1046/j.1463-5224.2001.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Suspected latent vertebral metastasis of uveal melanoma in a dog: a case report

Abstract: A six-year-old intact male Pomeranian was examined because of right eye discomfort. An iris neoplasm was suspected and the eye was enucleated. A uveal melanoma with malignant features was diagnosed. The dog recovered uneventfully from surgery. A general physical examination was performed at 3-month intervals afterwards without any detectable problem, but 18 months after the first presentation the dog suffered a rapid, progressive paraplegia. Radiographic examination and myelography revealed a spinal cord compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…to the heart and lungs,(69) spine (27) and brain (71) have also been reported in the canine species. In a case where brain metastasis occurred in a 13-year-old Cocker Spaniel, the tumor had spread from the iris and ciliary body to the choroid, optic nerve, and meninges.…”
Section: Anterior Uveamentioning
confidence: 93%
See 1 more Smart Citation
“…to the heart and lungs,(69) spine (27) and brain (71) have also been reported in the canine species. In a case where brain metastasis occurred in a 13-year-old Cocker Spaniel, the tumor had spread from the iris and ciliary body to the choroid, optic nerve, and meninges.…”
Section: Anterior Uveamentioning
confidence: 93%
“…(2) Fine needle aspiration of uveal masses is usually nondiagnostic. (26,27) Ultrasound-guided fine needle aspiration of a vitreal mass in a dog under anesthesia, has been previously described. (28) Cytology in that case revealed a moderate number of melanocytes, and histological examination of the exenterated globe confirmed that the mass was a choroidal melanoma.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…Primary canine uveal melanoma is considered to have a low risk for distant metastasis (Diters and others 1983, Dietz and others 1986, Wilcock and Peiffer 1986, Dubielzig 1990, Minami and Patnaik 1992, Giuliano and others 1999, Narstrom and Ekesten 1999, Rovesti and others 2001, Hyman and others 2002, Yi and others 2006) Thus, some 4 per cent of canine uveal melanomas metastasise (Rovesti and others 2001, Hyman and others 2002), usually by haematogenous route and generally within three months after diagnosis (Hyman and others 2002). In cats with ocular melanomas, the rate of metastasis may be as high as 60 per cent, and it may take years before clinical signs of metastatic disease become evident (Duncan and Peiffer 1991, Rovesti and others 2001, Harris and Dubielzig 2002). In human beings, melanoma is a common primary tumour that metastasises to the brain (Kirsch and others 2005, Naggara and others 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Uveal melanomas are classified as benign or malignant based on the basis of several criteria including morphological features of the neoplastic cells (Dubielzig 1990, Collinson and Peiffer 1993, Narstrom and Ekesten 1999), primary site of tumour origin, breed predilection, extent of ocular infiltration, mitotic index (Ryan and Diters 1984, Giuliano and others 1999), amount of cellular pleomorphism, degree of nuclear anaplasia, presence of tumour necrosis and prominent nucleoli (Hyman and others 2002). Reports show that mitotic index is the best criterion for histopathological classification of ocular melanomas of high metastatic potential (Wilcock and Peiffer 1986, Collinson and Peiffer 1993, Rovesti and others 2001). It has been suggested that a mitotic index greater than 4 is indicative of potential malignant biological behaviour (Diters and others 1983, Ryan and Diters 1984, Wilcock and Peiffer 1986, Rovesti and others 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation